Metal surface self-adaptive modified reinforced additive material and manufacturing process and method

Through adaptive modification of metal surfaces to strengthen additive materials and build the equipment online with extremely low friction self-lubricating environment, the problems of equipment friction wear and life extension are solved, the equipment surface anti-wear performance optimization and lubrication effect are improved, and energy consumption is reduced and operation and maintenance costs.

CN119320665APending Publication Date: 2025-01-17ZHIJU ROSE MOUNTAIN (SHANGHAI) TECHNOLOGY DEVELOPMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411303983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The prior art cannot effectively reduce friction and wear during equipment operation and extend the life of the equipment, especially the inability to realize online additive repair during the entire life cycle of the equipment, resulting in waste of energy and high operation and maintenance costs.

Method used

Using the method of adaptive modification of metal surface to strengthen additive materials and online construction of equipment with extremely low friction self-lubricating environment, through online intervention of functional materials, the friction energy is used to stimulate the interaction between functional materials and the motion sub-interface, and generate an anti-wear reinforcement layer to achieve Surface wear and additive compensation dynamic balance reduce friction wear, and improve lubrication effect through micro polishing modification of composite powder materials and solid-liquid multi-composite lubrication.

Benefits of technology

It realizes extremely low friction coefficient on the surface of the equipment, extends the equipment life, reduces energy consumption and operation and maintenance costs, has online dynamic adaptive management capabilities, can form high-hardness and low-roughness anti-wear layers on the friction pair surface, and optimizes the friction fit state , reduce vibration and noise.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320665A_ABST
    Figure CN119320665A_ABST
Patent Text Reader

Abstract

The invention relates to a metal surface self-adaptive modified reinforced additive material and a preparation process and method thereof, which are characterized in that silicate-containing natural minerals, amorphous carbon, SiO2, metal mixed powder, a curing agent, a defoaming agent, white grease and basic lubricating oil are mixed and stirred to react for 24-48 hours in a reaction kettle at 60 DEG C to generate a gel product. Through online intervention of functional materials, modification and reinforcement of additive materials, dynamic superfinishing and solid-liquid multi-component composite lubrication, an equipment extremely-low-friction self-lubricating environment is constructed, and the purposes of reinforcement of kinematic pair friction interface material performance, dynamic optimization of matching pair gaps, targeted repair of abrasion, reduction of friction abrasion, prolonging of the service life of equipment and improvement of the energy efficiency of the equipment are achieved. And the energy consumption and the operation and maintenance cost of the equipment in the whole life cycle are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material surface treatment engineering and lubrication engineering, and specifically relates to a metal surface adaptively modified and reinforced additive material, a manufacturing process, and a method for online construction of an extremely low friction self-lubricating environment for equipment. Background Art

[0002] During the equipment running-in and full life cycle, the material properties of the moving friction pair, the state and morphology of the interface, and the assembly clearance are very critical to the friction and wear rate, and are important factors that restrict the equipment's operating conditions, efficiency, service life, energy efficiency, and emission levels. According to statistics, about 1 / 3 of the world's disposable energy is wasted in the process of friction and wear, about 80% of mechanical parts failures are caused by friction and wear, and more than 50% of the serious accidents of mechanical equipment are caused by lubrication failure and excessive wear of various friction pairs such as gears, bearings, cylinder sleeves and pistons.

[0003] For a long time, the scientific and technological community has never stopped exploring ways to improve the operating efficiency and energy efficiency of friction pairs and extend their safe service life cycle. Improving the wear resistance of the surface of the matching pair material, controlling the clearance of the finished product and the wear rate of the matching pair are issues of great concern to engineers of mechanical equipment friction reduction and energy saving. In the design and processing stage, the ideal working state of the friction pair can be optimized through theoretical calculations, experimental simulations, etc. The surface characteristics of the friction pair can be improved through fine processing and surface coating technologies, which depend on material properties, processing accuracy and surface treatment methods. The matching pair assembly clearance depends on the processing accuracy (processing error) and assembly accuracy (assembly tolerance) of the parts and the increase in the matching pair clearance caused by friction, wear and thermal deformation during the relative motion of the kinematic pair. During the entire life cycle of the friction pair, under the influence of friction, the state parameters of the friction pair will continue to deteriorate, which is manifested in the gradual increase of friction coefficient, wear, energy consumption, vibration amplitude, vibration noise, friction pair clearance, lubricating medium loss, etc.; accordingly, the working efficiency of the friction pair, including thermal efficiency, kinetic energy transmission efficiency and power coefficient, will gradually deteriorate.

[0004] In the existing technology, friction and wear can only be reduced during the design life cycle of the equipment, but online additive repair of wear cannot be achieved. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for adaptively modifying and strengthening additive materials on metal surfaces and online constructing an extremely low friction self-lubricating environment for equipment (Metal Surface Adaptive Strengthening Technology, hereinafter referred to as "MAT"). Through the online intervention of functional materials, with the help of friction energy, the interaction between the functional materials and the kinematic pair interface is stimulated, and modification and strengthening and adaptive additive reactions occur to generate an anti-wear strengthening layer, thereby achieving a dynamic balance between surface wear and additive compensation; composite powder materials are adsorbed on the surface of the kinematic pair for filling and grinding, and the surface of the kinematic pair is micro-polished and modified to optimize the surface morphology of the kinematic pair, reduce friction factors, and play a role in super finishing; natural minerals containing silicates have a layered structure, and are solid lubricants together with amorphous carbon. They are adsorbed on the contact surface of the kinematic pair to play the role of ball bearings, forming solid-liquid multi-composite lubrication, and improving the lubrication effect.

[0006] Modified and enhanced additive manufacturing, dynamic super-finishing, and solid-liquid multi-composite lubrication have created an extremely low-friction self-lubricating environment for the equipment, enhanced the performance of the friction interface materials of the moving pairs, dynamically optimized the gap between the pairs, targetedly repaired wear, reduced friction and wear, extended the service life of the equipment, improved the energy efficiency of the equipment, and reduced the energy consumption and operation and maintenance costs of the equipment throughout its life cycle.

[0007] The present invention relates to a metal surface adaptively modified and reinforced additive material, which is characterized by being composed of the following materials in parts by weight:

[0008] (1) 5-10 parts of natural minerals containing silicates

[0009] (2) 10-15 parts of amorphous carbon

[0010] (3) SiO2 2-5 parts

[0011] (4) 2-5 parts of metal mixed powder (iron, copper, aluminum)

[0012] (5) 6-8 parts of curing agent

[0013] (6) 1-5 parts of defoaming agent

[0014] (7) 5-10 parts of white fat

[0015] (8) 90-100 parts of base lubricating oil.

[0016] The natural mineral particle size of silicate is 5 μm-600 nm. The metal mixed powder is composed of one or more metal mixed powders of iron, copper and aluminum, and the particle size of the powder is 10-20 nm.

[0017] The core component of the functional material of the present invention is a natural mineral aggregate containing silicate. During the reciprocating friction process of the friction pair, the micro-nano silicate composite functional powder particles with special activity dispersed in the lubricating medium enter the gap of the metal friction pair with the help of a transport carrier (engine oil, grease, etc.). They have abundant surface unsaturated charges and are easily adsorbed on the surface of the iron-based friction pair, and can effectively adsorb micro-nano metal wear debris and even ionic substances to participate in the friction reaction. Under the action of mechanochemistry, the mutual movement of the friction pair causes the microscopic protrusions on the contact surface to collide, cut (micro-polish), and squeeze each other. The collision point will produce an instantaneous flash temperature of 800-1200 degrees. The core powder particles of the micro-nano reinforced material undergo interlayer dissociation, in-situ phase change, and ion replacement during the adsorption, grinding, cutting, extrusion, and flash temperature process, generating new micro-nano particles with high density, high hardness, high melting point, and good thermal stability, which are fused to the concave seams and lattices of the friction pair surface matrix to grow new crystals. The Mg in the crystals 2+ Can be Fe 2+ Replacement forms a magnesium-iron solid solution, which is deposited and superimposed on the original surface of the friction pair with micro-nano particles such as metals in the environment (micro-smelting additive process), and fuses with the matrix to form an anti-wear strengthening layer.

[0018] Since the process of forming the strengthening layer of the surface self-reinforced material is a hard particle crystal deposition, pressure, high temperature "micro-smelting" and micro-polishing at the same time, the result is that an "Aurora" mirror strengthening layer is formed on the contact surface of the friction pair, and the contact surface of the moving pair changes from the original metal-metal contact friction to metal ceramic-metal ceramic contact friction. The two different matching surfaces show completely different tribological properties. The conventional friction process of friction, heat generation, fatigue and wear becomes a dynamic process of friction, heat generation, generation of strengthening layer, and adaptive micro-additive compensation for wear; after the surface roughness and dry friction coefficient are reduced, the oil film is more stable. Even if the instantaneous lubrication failure caused by the instantaneous break of the oil film due to various reasons, the new strengthening layer is harder, smoother, more resistant to high temperature and other better physical properties and extremely low friction coefficient, which can avoid the adverse results caused by instantaneous lubrication failure. Under cold start, high load and other use conditions, it can ensure that the friction parts are effectively protected against high load, lubrication failure and overheating, which will greatly reduce the failures such as cylinder pulling and shoe grinding, severe wear and tear caused by the high temperature of the friction pair surface caused by instantaneous oil film failure.

[0019] The metal surface adaptive modified and reinforced additive material of the present invention is a gel product formed by uniformly mixing natural minerals containing silicates, amorphous carbon, SiO2, metal mixed powder (iron, copper, aluminum), curing agent, defoaming agent, white fat, and base lubricating oil. The production process includes the following steps:

[0020] (1) Natural minerals containing silicates, amorphous carbon, SiO2, metal mixed powder (iron, copper, aluminum), a curing agent, and a defoaming agent are uniformly mixed to obtain a mixed powder;

[0021] (2) uniformly mixing the mixed powder, white fat and base lubricating oil to obtain a mixed liquid;

[0022] (3) The mixed solution is stirred and reacted in a reaction vessel at 60° C. for 24 to 48 hours to generate a gel product.

[0023] Gel products have better particle dispersibility and stability, and are easy to add into equipment lubricating media. They can quickly disperse powder particles in the lubricating medium and transport them to the contact surface of the moving pair.

[0024] The present invention relates to an online method for constructing an extremely low-friction self-lubricating environment for equipment (MAT), comprising the following steps:

[0025] (1) First, take a lubricating medium at a ratio of 1:10 and pre-dilute the gel product in the lubricating medium;

[0026] (2) Adding gel material to the lubricating medium of the target equipment at a ratio of 2-10‰ by weight according to the total amount of the lubricating medium of the target equipment;

[0027] (3) Before adding, first run the equipment for 10-20 minutes. In the hot state, pour the diluted gel material into the equipment lubricating oil tank three times, with an interval of 20-30 minutes in between;

[0028] (4) After all the additions are completed, continue to warm up the machine for 60 minutes, and then the equipment can directly enter normal operation.

[0029] The flash cladding additive process of the friction pair contact surface has adaptive characteristics. When the clearance of the kinematic pair is large, the wear is severe, and the surface morphology is relatively severely degraded, the friction is severe, the friction energy is high, the surface adsorption activity is strong, and the flash cladding additive speed is greater than the wear speed, which will automatically compensate for the wear tolerance. At this time, the friction pair surface behaves as a microscopic additive manufacturing process, or even negative wear; when the friction pair matching state tends to be optimized, the friction and wear are reduced, the friction energy is reduced, and the flash cladding additive speed is reduced. Under certain conditions of functional powder material concentration, load, relative motion speed and lubrication environment in the lubricating medium, the implementation of MAT friction management can achieve a relative dynamic balance between surface wear and additive compensation.

[0030] MAT functional powder material is also a solid lubricant. Its core component, layered silicate minerals, has a layered structure similar to conventional solid lubricants such as graphite and MoS2. It is mainly composed of Si-O tetrahedrons and Mg-O or Al-O octahedrons. The interlayer interaction type is hydrogen bond and van der Waals force. When subjected to extrusion and shear stress, it is easy to produce interlayer sliding, and then interlayer splitting and dissociation occur, which has good anti-extrusion and lubrication effects. At the same time, highly reactive silicate minerals have a catalytic effect, which can promote the carbon chain breakage of lubricating oils (greases), generate graphite with lubricating effects, and coat the surface of silicate particles. Solid lubrication and oil (grease) lubrication form a positive coupling, forming "oil (grease) multi-composite lubrication", which greatly improves the lubrication effect.

[0031] MAT functional powder material has the function of online dynamic micro-polishing. After the intervention of MAT functional powder, the functional powder particles adsorbed on the contact surface are first ground and refined on the contact surface of the moving pair, and the secondary particles and micro-nano metal particles will be adsorbed and stacked again and participate in the grinding, playing a supporting and barrier role between the moving friction pairs, slowing down the collision and extrusion of micro-protrusions, and reducing friction and wear. At the same time, the powder particles will also clean the oil stains in the fine cracks and pits on the moving contact surface during the grinding process, adsorb and fill beneficial particles, fill unevenness, and perform micro-polishing modification on the metal surface, cut peaks and fill valleys, optimize surface morphology, reduce friction coefficient, and play a dynamic super-finishing role. In the friction and wear comparison experiment of iron-based metal friction pairs under oil lubrication experimental conditions, atomic force microscopy analysis shows that after adding MAT functional powder, the peaks and valleys of the experimental surface are greatly reduced, and the surface roughness is greatly reduced. Implementing MAT treatment during the running-in period of new equipment can reduce friction and wear, shorten the running-in period, and extend the life of moving parts.

[0032] According to the total amount of lubricating medium of the target equipment, add gel material to the lubricating medium of the equipment at a ratio of 2-10‰ by weight. Before adding, take the lubricating medium at a ratio of 1:10 and pre-dilute the gel material in the lubricating medium. First, run the equipment for 10-20 minutes. In the hot state, pour the diluted gel material into the equipment lubricating oil tank three times, with an interval of 20-30 minutes in between. After all the additions are completed, continue to run the hot machine for 60 minutes, and the equipment can directly enter the normal operation state.

[0033] Through the online intervention of functional materials and the use of friction energy, the interaction between the functional materials and the kinematic pair interface is stimulated, and modified strengthening and adaptive additive reactions occur to generate an anti-wear strengthening layer, thereby achieving a dynamic balance between surface wear and additive compensation; the composite powder material is adsorbed on the kinematic pair surface for filling and grinding, and the kinematic pair surface is micro-polished to optimize the kinematic pair surface morphology, reduce friction factors, and play a role in super finishing; natural minerals containing silicates have a layered structure, and are solid lubricants like amorphous carbon. They are adsorbed on the contact surface of the kinematic pair, play the role of ball bearings, and constitute solid-liquid multi-composite lubrication, which improves the lubrication effect.

[0034] Modified and enhanced additive manufacturing, dynamic super-finishing, and solid-liquid multi-composite lubrication have created an extremely low-friction self-lubricating environment for the equipment, enhanced the performance of the friction interface materials of the moving pairs, dynamically optimized the gap between the pairs, targetedly repaired wear, reduced friction and wear, extended the service life of the equipment, improved the energy efficiency of the equipment, and reduced the energy consumption and operation and maintenance costs of the equipment throughout its life cycle.

[0035] The present invention has the following positive effects:

[0036] (1) The self-generated strengthening material of the friction pair surface of the present invention generates a modified strengthening layer with superior tribological properties on the contact surface of the friction pair during the process of micro-smelting, micro-nano material addition and micro-polishing. The modified strengthening layer has extraordinary mechanical and physical properties, such as extremely low friction coefficient, extremely low surface roughness, high hardness, insulation, pressure resistance, impact resistance, high temperature resistance, corrosion resistance, etc. The metallographic structure, chemical composition, performance, strength, size and morphology of the friction pair surface are changed in the microstructure to form a wear-resistant surface with high hardness, high elastic modulus, low roughness and low friction coefficient, and the microstructure optimization of the surface state and the fitting clearance is achieved, thereby changing the friction fitting state of the fitting pair, reducing friction, vibration and noise, and extending the service life of parts;

[0037] (2) The present invention has the characteristics of online, dynamic self-adaptation, no shedding of the strengthening layer, and completion of the treatment cycle without affecting the replacement of the lubricating medium. The treatment process is completed online without disassembling the equipment. The thickness and speed of the surface material addition depend on the friction heat energy, and can be dynamically adjusted according to the friction and wear state. It has a nearly intelligent "adaptive" control feature, that is, when the friction pair approaches or reaches the optimal matching clearance, it will not continue to increase the size of one of the surfaces indefinitely to deteriorate the friction state. When the size of the friction pair is repaired to approach or reach the optimal matching clearance, its surface reconstruction rate and wear rate reach a dynamic balance at this limit level, and the tribological state automatically maintains the best without manual intervention;

[0038] (3) The modified strengthening layer is a new heterogeneous gradient nanostructured hardened layer formed on the surface of the original matrix. The hardness gradually increases from the relatively soft and uniform basis of the matrix to the superhard surface layer. It diffuses and melts with the matrix material into one, forming a tight metallurgical solidification bond with the same thermal linear expansion coefficient. There is no obvious physical interface and it will not fall off due to external force. After the treatment cycle is completed, the strengthening layer has extremely high wear resistance and has long-lasting activity, so changing the lubricating medium will not affect the effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a comparison diagram of the sample surface before and after the implementation of Example 4 of the present invention;

[0040] Figure 2 This is a comparison chart of test data of Example 6 of the present invention. DETAILED DESCRIPTION

[0041] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0042] Embodiment 1:

[0043] (1) 5 parts of natural silicate minerals with a particle size of 10.00 μm, 15 parts of amorphous carbon powder with a particle size of 10 nm, 15 parts of copper powder with a particle size of 10 nm, 10 parts of iron powder with a particle size of 10 nm, and 10 parts of SiO2 with a particle size of 600 nm were mixed to obtain a mixed powder;

[0044] (2) The mixed powder was mixed evenly with 96 parts of Kluber grease to prepare a mixed grease;

[0045] (3) Injecting the mixed grease into the gear box of the cutter head of the gantry milling machine;

[0046] (4) Gearbox vibration is reduced by 30% and the service life is extended by 3 times.

[0047] Embodiment 2:

[0048] (1) 10 parts of a silicate-containing natural mineral with a particle size of 2.00 μm, 5 parts of amorphous carbon with a particle size of 10 nm, and iron powder with a particle size of 10 nm are mixed to obtain a mixed powder;

[0049] (2) uniformly mixing the mixed powder with 100 parts of base lubricating oil and 50 parts of white fat to prepare a gel;

[0050] (3) The gel is used as the lubricating medium for the RV reducer of the industrial robot, and the service life of the bearings and gears of the RV reducer is extended by 1 times;

[0051] Embodiment 3:

[0052] (1) 5 parts of natural silicate minerals with a particle size of 2.00 μm, 15 parts of amorphous carbon powder with a particle size of 10 nm, 15 parts of aluminum powder with a particle size of 10 nm, 10 parts of iron powder with a particle size of 10 nm, 10 parts of SiO2 with a particle size of 600 nm, and graphite with a particle size of 600 nm are mixed to obtain a mixed powder;

[0053] (2) uniformly mixing the mixed powder with 100 parts of base lubricating oil to prepare a gel mixture;

[0054] (3) First, take automobile engine lubricating oil at a ratio of 1:10 and pre-dilute the gel product in the lubricating oil;

[0055] (4) Adding gel material to the engine lubricating oil at a ratio of 2-10‰ by weight based on the total amount of lubricating oil in the engine;

[0056] (5) Before adding, let the car idle for 10-20 minutes. When the engine is hot, pour the diluted gel material into the engine oil tank three times, with an interval of 20-30 minutes in between.

[0057] (6) After all the additions are completed, run at idle speed for another 60 minutes;

[0058] (7) The cylinder pressure of automobile engines increased by 27%, the service life of lubricating oil was extended by 1.5 times, and fuel consumption was reduced by 5.7%.

[0059] Embodiment 4:

[0060] The mixed solution prepared in Example 2 was sprayed on the surface of the friction pair of the sample, and a ring-disk friction and wear test was carried out on a friction and wear testing machine. Figure 1 As shown (the left side is the metallographic image of the unsprayed mixed solution, and the right side is the metallographic image of the sprayed mixed solution), the results show that after adding the metal surface autogenous strengthening material of the present invention, the friction coefficient of the sample is reduced from 0.11 to 0.04, the surface hardness is increased by about 30% compared with before implementation, and the roughness becomes smooth;

[0061] Embodiment 5:

[0062] The mixed liquid prepared in Example 3 was used to treat the crankshaft connecting rod neck surface of a locomotive diesel engine. The test data are shown in the following table:

[0063]

[0064] As can be seen from the table above, the average wear of the crankshaft connecting rod neck was 0.02 mm in the first overhaul period before treatment, and the average wear was reduced to 0.0001 mm after treatment, which means there was almost no wear. Therefore, the surface autogenous strengthening material of the present invention is used in many diesel locomotives, and the friction pair strengthening surface after treatment shows very outstanding anti-wear performance.

[0065] Embodiment 6:

[0066] The mixed liquid prepared in Example 3 was used to treat the DL96-305 crankshaft of the DF4B type 3885 locomotive No. 1088 diesel engine of the Hangzhou Locomotive Depot. The test data are as follows: Figure 2 As shown, the crankshaft main journal wears an average of 0.04mm and the connecting rod journal wears an average of 0.0156mm during the first repair after the overhaul. MAT treatment was implemented when the second repair period reached 2 / 3 of the mileage. During the second repair, the crankshaft main journal wears slightly -0.014mm (negative wear) and the connecting rod journal wears -0.0012mm (negative wear). Compared with the wear speed of the first repair, the main journal should have worn at least 0.026mm and the connecting rod journal should have worn more than 0.01mm after running to 2 / 3 of the mileage. After the implementation of MAT treatment, the main journal began to be repaired by additives under the action of MAT particles. After a period of repair, the main journal not only returned to the factory size, but also showed negative wear, that is, the main journal increased by 0.014mm and the connecting rod journal increased by 0.0012mm relative to the factory loading size.

[0067] The DF7C type 5023 locomotive 021 diesel engine 97-275-40 crankshaft, DF7C type 5074 locomotive 0167 diesel engine 0101002EQ crankshaft, DF7C type 5189 locomotive 222 diesel engine 9908060EQ crankshaft, DF7C type 5236 locomotive 095 diesel engine 98275-46 crankshaft all showed negative wear in the Hangzhou section. Analysis shows that after running to 2 / 3 of the mileage, the crankshaft neck and the bearing bushing were worn, and the matching clearance between the shaft and the bushing has exceeded the matching clearance during assembly. The MAT treatment of the present invention was implemented. Because the MAT did not repair the steel-backed aluminum bushing significantly, it left a larger space for additive repair of the journal, so the journal showed relatively large negative wear, proving the additive repair function of the MAT.

[0068] To summarize the above analysis, the effects of the metal surface adaptively modified and strengthened additive material and the online construction equipment ultra-low friction self-lubricating environment method of the present invention on the surface of the metal friction pair can be summarized as dispersion strengthening, fine grain strengthening, morphology strengthening, low friction coefficient hard layer strengthening, etc. After interacting with the metal friction pair, a wear-resistant surface with high hardness, high elastic modulus, high temperature resistance, low roughness and low friction coefficient is formed on the surface of the friction pair, optimizing the surface anti-wear performance and matching clearance of the friction pair, constructing a solid-liquid multi-lubricating environment, reducing friction and wear, and extending the service life of the equipment, and finally taking friction reduction, wear reduction, additives, repair, cost reduction, consumption reduction, energy saving, and carbon reduction as a comprehensive embodiment.

[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A metal surface adaptively modified and strengthened additive material, characterized in that: It is composed of the following materials in parts by weight: 5-10 parts of natural minerals containing silicates Amorphous carbon 10-15 parts SiO2 2-5 parts 2-5 parts of metal mixed powder 6-8 parts of curing agent Defoaming agent 1-5 parts 5-10 parts of white fat Lubricant 90-100 parts.

2. The metal surface adaptively modified and reinforced additive material according to claim 1, characterized in that: The metal mixed powder is composed of one or more of iron, copper and aluminum powders.

3. The metal surface adaptively modified and reinforced additive material according to claim 2, characterized in that: The particle size of the metal powder is 10-20 nm.

4. The metal surface adaptively modified and reinforced additive material according to claim 1, characterized in that: The particle size of the natural silicate-containing mineral is 5 μm-600 nm.

5. The metal surface adaptively modified and strengthened additive material according to claim 1, characterized in that: The curing agent is an amide amine curing agent.

6. The metal surface adaptively modified and strengthened additive material according to claim 1, characterized in that: The defoamer is a polyether defoamer.

7. The metal surface adaptively modified and strengthened additive material according to claim 1, characterized in that: The lubricating oil adopts base lubricating oil.

8. The process for producing a metal surface adaptively modified and reinforced additive material according to any one of claims 1 to 7, characterized in that: The steps include: (1) Natural minerals containing silicates, amorphous carbon, SiO2, metal mixed powder, a curing agent, and a defoaming agent are uniformly mixed to obtain a mixed powder; (2) uniformly mixing the mixed powder, white fat and base lubricating oil to obtain a mixed liquid; (3) The mixed solution is stirred and reacted in a reaction vessel at 60° C. for 24 to 48 hours to generate a gel product.

9. A method for online construction of an extremely low friction self-lubricating environment for equipment, using the self-generated strengthening material gel product of the friction pair surface as claimed in claim 8, added to the equipment lubricating medium, comprising the following steps: (1) First, take a lubricating medium at a ratio of 1:10 and pre-dilute the gel product in the lubricating medium; (2) Adding gel material to the lubricating medium of the target equipment at a ratio of 2-10‰ by weight according to the total amount of the lubricating medium of the target equipment; (3) Before adding, first run the equipment for 10-20 minutes. In the hot state, pour the diluted gel material into the equipment lubricating oil tank three times, with an interval of 20-30 minutes in between; (4) After all the additions are completed, continue to warm up the machine for 60 minutes, and then the equipment can directly enter normal operation.

Citation Information

Cited By

  • Steel-plastic composite oil distribution ring for wind driven generator and preparation method of steel-plastic composite oil distribution ring

    CN121162667A